Interactive Powerpoint Media Integrated with the Problem Based Learning Model to Facilitate the Strengthening of Critical Reasoning and Independence Dimensions of Grade IV Elementary School Students - Farah Labibah; Sri Untari; Oktaviani Adhi Suciptaningsih (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
The implementation of Problem Based Learning (PBL) in elementary schools is often limited by the lack of interactive learning media, resulting in suboptimal development of students’ critical reasoning and learning independence. This gap highlights the need for instructional media that effectively supports PBL while actively engaging students in meaningful learning processes. This study aims to develop an interactive PowerPoint media integrated with PBL syntax that is valid, practical, and effective in enhancing students’ critical reasoning and learning independence. The study adopts the Lee & Owens development model, which includes analysis, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, questionnaires, tests, and documentation. Data were analyzed using descriptive statistics and N-Gain to determine effectiveness, while qualitative data were analyzed using an interpretative approach based on Stake (1995). The results show that the developed media meets validity criteria based on expert judgment and demonstrates high practicality in both teacher and student responses. In terms of effectiveness, the media improves students’ critical reasoning skills, as indicated by a high N-Gain value (0.73). In addition, students’ learning independence reaches a high level, with most students categorized as highly independent. The novelty of this study lies in the integration of structured PBL syntax into interactive PowerPoint media to simultaneously enhance critical reasoning and learning independence in elementary school contexts. Overall, the developed media is feasible, practical, and effective for supporting PBL-based learning in elementary education.